Simian virus 40 early- and late-region promoter functions are enhanced by the 72-base-pair repeat inserted at distant locations and inverted orientations. - Fromm, M (1983)
Tandemly repeated 72-base-pair (bp) segments located between nucleotides 107 and 250 of the simian virus 40 genome are essential for early region transcription. The functional requirement for the 72-bp repeat was supplied even when that segment was translocated to several locations distant from, and in different orientation, relative to, the promoter. Regardless of the position of the 72-bp enhancer segment, transcription was initiated at the same locations as with the normal promoter. Translocation of the 72-bp repeat segment to other sites in the genome resulted in the appearance of DNase I hypersensitivity at that site in the intranuclear viral minichromosomes. One of the translocations which did not produce enhancement of early- and late-region expression also failed to create a DNase I-hypersensitive site at the translocated 72-bp segment.